Characterization Of Antioxidant Peptides Of Soybean Protein Hydrolysate - Abu-Salem, Ferial M.; Mahmoud, Marwa H.; M. H. El-Kalyoub; A. Y. Gibriel; Azza Abou-Arab (Zenodo, 2013)
In order to characterize the soy protein hydrolysate obtained in this study, gel chromatography on Sephadex G-25 was used to perform the separation of the peptide mixture and electrophoresis in SDS-polyacrylamide gel has been employed. Protein hydrolysate gave high antioxidant activities, but didn't give any antimicrobial activities. The antioxidant activities of protein hydrolysate was in the same trend of peptide content which gave high antioxidant activities and high peptide content between fractions 15 to 50. With increasing peptide concentrations, the scavenging effect on DPPH radical increased until about 70%, thereafter reaching a plateau. In compare to different concentrations of BHA, which exhibited higher activity (90%), soybean protein hydrolysate exhibited high antioxidant activities (70%) at a concentration of 1.45 mg/ml at fraction 25. Electrophoresis analysis indicated that, low- MW hydrolysate fractions (F1) appeared, on average, to have higher DPPH scavenging activities than high-MW fractions. These results revealed that soybean peptides probably contain substances that were proton donors and could react with free radicals to convert them to stable diamagnetic molecules. : {"references": ["", "P. Kehrer, \"Free radicals as mediators of tissue injury and disease.\"\nCritical Rev in Toxic., vol. 23, pp. 21\u201348, 1993.", "N. Baydar, G. O\u00a8 zkan, and S. Yasar, \"Evaluation of the antiradical and\nantioxidant potential of grape extracts,\" Food Control, vol.18, pp. 1131\u2013\n1136, 2007.", "N. Rajapakse, E. Mendis, W. K. Jung, J. Y. Je, and S.K. Kim,\n\"Purification of a radical scavenging peptide from fermented mussel\nsauce and its antioxidant properties,\" Food Research International, vol.\n38, pp.175\u2013182, 2005.", "R. Marcuse, \"Antioxidative effect of amino acids,\" Nature, vol.186,\npp.886-887, 1960.", "A. Saiga, S. Tanabe, and T. Nishimura, \"Antioxidant activity of peptides\nobtained from porcine myofibrilar proteins by proteasetreatment,\" J.\nAgriculture Food Chemistry, vol.51, no. 12, pp.3661\u20133667, 2003.", "S. Morimura, H. Nagata, Y. Uemura, A. Fahmi, T. Shigematsu and K.\nKida, \"Development of an effective process for utilization of collagen\nfrom livestock and fish waste,\" Process Biochemistry, vol.37, no. 12, pp.\n1403\u20131412, 2002.", "S. Sakanaka, Y. Tachibana, N. Ishihara, and LR. Juneja, \"Antioxidant\nactivity of egg-yolk protein hydrolyzates in a linoleic acid oxidation\nsystem,\" Food Chemistry, vol. 86, no. 1,pp. 99\u2013103, 2004.", "F. Shahidi, and R. Amarowicz, \"Antioxidant activity of protein\nhydrolyzates from aquatic species,\" J. American Oil Chemistry Society,\nvol.73, no. 9, pp. 1197\u20131199, 1996.", "Y. Je, P.Y. Park, and S.K. Kim, \"Antioxidant activity of a peptide\nisolated from Alaska Pollack (Theragra chalcogramma) frame protein\nhydrolysate,\" Food Res Int , vol.38, pp .45\u201350, 2005.\n[10] R. E. Aluko, and E. Monu, \"Functional and bioactive properties of\nquinoa seed protein hydrolyzates,\" J. of Food Science, vol. 68, no. 4, pp.\n1254\u20131258, 2003.\n[11] B.F. Gibbs, A. Zougman, R. Masse, and C. Mulligan, \"Production and\ncharacterization of bioactive peptides from soy hydrolysate and soyfermented\nfood,\" Food Research International, vol. 37, no. 2, pp. 123\u2013\n131, 2004.\n[12] H.M. Chen, K. Muramoto, F. Yamauchi, and K. Nokihara, \"Antioxidant\nactivity of designed peptides based on the antioxidative peptide isolated\nfrom digests of a soybean protein,\" J. Agriculture Food Chemistry, vol.\n44, no. 9, pp.2126\u20132130, 1996.\n[13] H.M. Chen, K. Muramoto, F. Yamauchi, K. Fujimoto, and K. Nokihara,\n\"Antioxidative properties of histidine-containing peptides designed from\npeptide fragments found in the digests of a soybean protein,\" J.\nAgriculture Food Chemistry, vol. 46, no. 1, pp. 49\u201353, 1998.\n[14] W.D. Chiang, C.J. Shih, and Y.H. Chu, \"Functional properties of soy\nprotein hydrolysate produced from a continuous membrane reactor\nsystem,\" Food Chemistry, vol. 65, no. 2, pp. 189\u2013194, 1999.\n[15] E.N. Frankel and A. Meyer, \"The problems of using one-dimensional\nmethods to evaluate multifunctional food and biological antioxidants,\" J.\nScience Food Agriculture, vol. 23, 80, no. 13, pp. 1925\u20131941, 2000.\n[16] C. Sa\u00b4nchez-Moreno, \"Methods used to evaluate the free radical\nscavenging activity in foods and biological systems,\" Food Science\nTechnology International, vol. 8, no. 3, pp. 121\u2013137, 2002.\n[17] E.A. Pen\u02dca-Ramos, and Y.L. Xiong, \"Antioxidant activity of soy protein\nhydrolyzates in a liposomial system,\" J. of Food Science, vol. 6, no. 8,\npp. 2952\u20132956, 2002.\n[18] A. Arnoldi, A. D'Agostina, G. Boschin, M.R. Lovati, C. Manzoni, and\nC.R. Sirtori, \"Soy protein components active in the regulation of\ncholesterol homeostasis. In: Biologically active phytochemicals in\nfood,\" Royal Society of Chemistry, vol. 269, pp. 103\u2013106, 2001.\n[19] J.R. Chen, S.C. Yang, K. Suetsuna, and J.C.J. Chao, \"Soybean proteinderived\nhydrolysate affects blood pressure in spontaneously\nhypertensive rats,\" J. Food Biochemistry, vol. 28, no. 1, pp. 61\u201373,\n2004.\n[20] H.M. Chen, K. Muramoto, and F. Yamauchi, \"Structural analysis of\nantioxidative peptides from soybean b-conglycinin,\" Agriculture Food\nChemistry, vol. 43, no. 3, pp. 574\u2013578, 1995.\n[21] W.C. Hou, H.J. Chen, and Y.H. Lin, Antioxidant peptides with\nangiotensin converting enzyme inhibitory activities and applications for\nangiotensin converting enzyme purification,\".J. Agriculture Food\nChemistry, vol. 51, pp. 1706-1709, 2003.\n[22] Y.P. Zhu, J.F. Fan, Y.Q. Cheng, and L.T. Li, \"Improvement of the\nantioxidant activity of Chinese traditional fermented okara (Meitauza)\nusing Bacillus subtilis B2, \"Food Control, vol. 19, pp.654-661, 2008.\n[23] C. Wang, Q. Ma, S. Pagadala, M.S. Sherrard, and P.G. Krishnan,\n\"Changes of Isoflavones during Processing of Soy Protein Isolates,\" J.\nAmerican Oil Chemistry Society, vol. 75, no. 3, pp. 337-341, 1998.\n[24] J. Adler-Nissen, \"Determination of degree of hydrolysis of food protein\nhydrolysates by trinitrobenzenesulfonic acid,\" J. Agriculture. Food\nChemistry, vol. 27, pp. 1256-1262, 1979.\n[25] F.M. Netto, and M.A.M. Galeazzi, \"Production and characterization of\nenzymatic hydrolysate from soy protein isolate,\" Lebensm.-wiss. U.-\nTechnol, vol. 31, pp. 624-631, 1998.\n[26] K.A. Lee and S.H. Kim, \"SSGE and DEE, new peptides isolated from a\nsoy protein hydrolysate that inhibit platelet aggregation,\" Food\nChemistry, vol. 90, pp. 389-393, 2005.\n[27] C. Mar\u0131\u00b4a, S. Conde, A. Adriana, and C. An\u02dco\u00b4n, \"Characterization of\namaranth proteins modified by trypsin proteolysis. Structural and\nfunctional changes,\" LWT - Food Science and Technology, vol. 42, pp.\n963\u2013970, 2009.\n[28] SAS. \"SAS User's Guide: Statistics,\" SAS Inc., Cary, NC, 1982.\n[29] W. R. Waller and D.B. Duncan, \"A Bayes rule for the symmetric\nmultiple comparison problems,\" J. of the American Statistical\nAssociation, vol. 64, pp. 1481-1503, 1969.\n[30] S.B. Zhang, Z. Wang, and S.Y. Xu, \"Antioxidant and Antithrombotic\nActivities of Rapeseed Peptides,\" J. American Oil Chemistry Society,\nvol. 85, pp. 521\u2013527, 2008.\n[31] Y. Yoshie Starka, Y. Wadab, M. Schottb, and A. Wasche, \"Functional\nand bioactive properties of rapeseed protein concentrates and sensory\nanalysis of food application with rapeseed protein concentrates,\" LWT,\nvol. 39, pp. 503\u2013512, 2006.\n[32] K. Saito, D.H. Jin, T. Ogawa, K. Muramoto, E. Hatakeyama, and T.\nYasuhara, \"Antioxidative properties of tripeptide libraries prepared by\nthe combinatorial chemistry,\" J. Agriculture Food Chemistry, vol. 51,\nno. 12, pp. 3668-3674, 2003."]}